2003
DOI: 10.1007/s00132-002-0441-7
|View full text |Cite
|
Sign up to set email alerts
|

Der Einfluss der Femur- und Tibiakomponentenrotation auf das patellofemorale Versagen beim k�nstlichen Kniegelenkersatz

Abstract: Patellofemoral complications are among the most common causes for revision surgery in total knee arthroplasty. So far no quantitative assessment has been made of the femoral and tibial malalignment or the positioning of the patellar component and the type of patellofemoral complication or failure. In particular, no comparative studies are available that include patients with and without patellofemoral failure in respect to the above-mentioned parameters when implant material, implant design, and fixation techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…Malposition of prosthetic components is one of the most important factors leading to failure of TKA [15,24-28]. Chowdhury et al [29] showed that external rotation of the tibial component of 15° caused posteromedial and anterolateral impingement.…”
Section: Discussionmentioning
confidence: 99%
“…Malposition of prosthetic components is one of the most important factors leading to failure of TKA [15,24-28]. Chowdhury et al [29] showed that external rotation of the tibial component of 15° caused posteromedial and anterolateral impingement.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective randomised study, Pagnano et al [24] showed that a rotating platform knee design did not decrease the prevalence of lateral retinacular release, patellar tilt or subluxation in comparison to a posterior-stabilised, fixedbearing knee [23]. A few radiological studies ascribe altered patellofemoral kinematics and the appearance of anterior knee pain to combined femoral and tibial component internal rotation [2,5]. In our study different combinations of femoral and tibial component alignment could not show a significant effect of tibial component rotation or combined component rotation on patellofemoral kinematics.…”
Section: Discussionmentioning
confidence: 98%
“…Several authors emphasise that the appearance of patellar maltracking is caused by rotational malalignment of the femoral and tibial components [4][5][6][7][8][9][10][11]. Furthermore, especially internal rotation of the femoral component seems to contribute to altered patellofemoral kinematics and consequently the occurrence of anterior knee pain [2,12,13]. In a radiological study, Berger et al [12] state that combined internal rotation of the femoral and tibial components correlates directly with the severity of postoperative patellofemoral complications.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Als eine der Hauptursachen wird ein unphysiologischer Patellalauf mit konsekutiv pathologischer Druckerhöhung im Bereich des Patellofemoralgelenkes genannt [9,12].…”
Section: Introductionunclassified